A multicenter phase II randomized trial of durvalumab (MEDI‐4736) versus physician's choice chemotherapy in recurrent ovarian clear cell adenocarcinoma (MOCCA). Issue 8 (August 2020) - Ngoi, Natalie YL; Heong, Valerie; Ow, Samuel; Chay, Wen Yee; Kim, Hee Seung; Choi, Chel Hun; Goss, Geraldine; Goh, Jeffrey C; Tai, Bee Choo; Lim, Diana GZ; Kaliaperumal, Nivashini; Au, Veonice B; et al.
ABSTRACT : Background : The optimal treatment of recurrent ovarian clear cell carcinoma remains unknown. There is increasing rationale to support the role of immune checkpoint inhibitors targeting the programmed cell death protein 1 (PD‐1)/programmed death‐ligand 1 (PD‐L1) axis in ovarian clear cell carcinoma. Primary objective : To evaluate the efficacy of durvalumab (MEDI‐4736) compared with standard chemotherapy in patients with recurrent ovarian clear cell carcinoma. Study hypothesis : Patients with recurrent ovarian clear cell carcinoma treated with durvalumab will have improved progression‐free survival compared with those treated with chemotherapy of physician's choice. Trial design : The MOCCA study is a multicenter, open‐label, randomized phase II trial in patients with recurrent ovarian clear cell carcinoma, which recruited from eight sites across Gynecologic Cancer Group Singapore (GCGS), Korean Gynecologic‐Oncology Group (KGOG), and Australia New Zealand Gynecological Oncology Group (ANZGOG). Enrolled patients were randomized in a 2:1 ratio to receive durvalumab or physician's choice of chemotherapy until disease progression, intolerable toxicity, or withdrawal of patient consent. Major inclusion/exclusion criteria : Eligible patients required histologically documented diagnosis of recurrent ovarian clear cell carcinoma, as evidenced by WT1 negativity. All patients must have been of Eastern Cooperative Oncology Group (ECOG) performance status 2 or better, and have had previous treatment with, and progressed or recurred after prior platinum‐based chemotherapy. No more than four prior lines of treatment were allowed and prior immune checkpoint inhibitor treatment was not permitted. Primary endpoints : The primary endpoint was the median progression‐free survival following treatment with durvalumab, compared with physician's choice of chemotherapy. Progression‐free survival was defined as the time from the first day of treatment to the first observation of disease progression, or death due to any cause, or last follow‐up. Sample size : The target sample size was 46 patients. Estimated dates for completing accrual and presenting results : Accrual has been completed and results are expected to be presented by mid‐2021. Trial registration : Clinicaltrials.gov: NCT03405454 .